A European survey on the insights of patients living with metastatic colorectal cancer: the patient journey before, during and after diagnosis - an Eastern European perspective. Issue 5 (30th September 2020) - Maravic, Zorana; Rawicka, Iga; Benedict, Agnes; Wyrwicz, Lucjan; Horvath, Anna; Fotaki, Vassiliki; Carrato, Alfredo; Borras, Josep M; Ruiz-Casado, Ana; Petrányi, Agota; Lemmens, Liesbeth; Espín-Basany, Eloy; et al.
Abstract : Background: Despite being highly preventable and treatable if diagnosed early, colorectal cancer (CRC) remains the second leading cause of cancer-related death in Europe. Limited information is available from the patient perspective on the persisting unmet needs of the journey of the patient with CRC. Objective: To capture European metastatic CRC (mCRC) patients' insights during the patient journey (prediagnosis; diagnosis; postdiagnosis) through a patient survey. Methods: In total, 883 patients from 15 European countries participated. Participants were divided into four groups from Hungary, Poland, Serbia and 'other European countries' (n=103, 163, 170 and 447 patients, respectively). Results: General awareness of CRC and its symptoms prediagnosis varied among groups, with patients from Poland recording the lowest levels. Screening practices and attitudes also varied; while more patients from Serbia had been invited to CRC screening (~15%) compared with the other groups, the ones not invited claimed mostly (~20%) that would not have attended if they had been invited. Whereas most patients were diagnosed within a month after the first consultation/positive screening, the percentages varied substantially being lowest among patients in Poland (~30%) and Serbia (~25%). Although CRC-related information provision varied, with most informed patients from Hungary (~90%) and least from Serbia (~50%), all groups requested an easier-to-understand language by the healthcare team. Approximately 50% of patients from Eastern Europe had to wait longer than a month to receive treatment, in contrast to ~30% from other European countries. All groups emphasised the unmet need for support from psychologists and other patients. Conclusions: Our survey reveals the key aspects of the journey of the patient with mCRC and highlights the areas of similarities and differences between patients with mCRC from Eastern Europe versus those from other European countries as well as among patients from different Eastern European countries, calling for improvement particularly around awareness, screening, treatment availability, communication and support networks.